Becoming an emsee : the 7 principles of rap - Savánt, O'hene (Diasporic Africa Press, 2020)
As the world celebrates Hip Hop with the Pulitzer Prize and title of "first billionaire rapper," what is lost in the noise of recognition is the craft, artistry, and techniques of Hip-Hop music or rapping. Hailed as a "genius" by Dr. Cornel West and acknowledged as one of the most innovative musicians by Hip-Hop legends and icons of rap, O'hene Savànt redefines the rapper as an "emsee"--an artist with vision and not simply rote technique. In Becoming an Emsee, the multi-instrumentalist, producer, and Hip-Hop artist Savànt offers the rapper and anyone who wants to learn the art of emseeing a first-of-its-kind guide, organized into seven principles and packed with original insights for every artist from a master musician. It is one thing to rap, but it is quite another to know how to rap and then teach it. Becoming an Emsee introduce readers to philosophies that lay at the foundation of rap as well as disc jockeys, jazz musicians, and other Hip-Hop pioneers. Lyrics from Savànt and a range of rappers are analyzed to show technique, evolution and the musical structures underlying rhymes, while immersing us in the art of composition, wit, word manipulation, voicing, flow, and live performance. Through Becoming an Emsee, Savànt reclaims the craft, artistry and musicianship of Hip-Hop music.